152 State Street, July 30, 1975 - Unknown (Tufts Archival Research Center, 2005)
Elevated view northwest of 152 State Street, located between Catham Row to the west-southwest and Commercial Street to the east-northeast. Signage and awnings adorn the facade of the building. Automobiles fill State Street, and pedestrians are included in the photograph. 4 15/16 x 3 1/2 Photographs